Athyrium bipinnatum K.Hori (Athyriaceae), a new cornopteroid fern from Japan - Kiyotaka Hori (PhytoKeys, 2020)
I describe Athyrium bipinnatum sp. nov. and discuss morphological differences between closely related species. The new species is endemic to Japan, occurring on the islands of Honshu, Kyushu, and Shikoku. Based on the criteria of the International union for conservation of nature and natural resources, this new species is here considered endangered.